Explaining intraspecific diversity in plant secondary metabolites in an ecological context. Issue 3 (1st October 2013) - Moore, Ben D.; Andrew, Rose L.; Külheim, Carsten; Foley, William J.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> 733 I. I. 733 II. II. 734 III. III. 735 IV. IV. 735 V. V. 735 VI. VI. 737 VII. VII. 739 VIII. VIII. 740 IX. IX. 742 X. X. 744 745 References 745 </table-wrap> Summary Plant secondary metabolites (PSMs) are ubiquitous in plants and play many ecological roles. Each compound can vary in presence and/or quantity, and the composition of the mixture of chemicals can vary, such that chemodiversity can be partitioned within and among individuals. Plant ontogeny and environmental and genetic variation are recognized as sources of chemical variation, but recent advances in understanding the molecular basis of variation may allow the future deployment of isogenic mutants to test the specific adaptive function of variation in PSMs. An important consequence of high intraspecific variation is the capacity to evolve rapidly. It is becoming increasingly clear that trait variance linked to both macro‐ and micro‐environmental variation can also evolve and may respond more strongly to selection than mean trait values. This research, which is in its infancy in plants, highlights what could be a missing piece of the picture of PSM evolution. PSM polymorphisms are probably maintained by multiple selective forces acting across many spatial and temporal scales, but convincing examples that recognize the diversity of plant population structures are rare. We describe how diversity can be inherently beneficial for plants and suggest fruitful avenues for future research to untangle the causes and consequences of intraspecific variation.